RESPONSE OF VILLAGE COUNCILS TO THE FOOD DIVERSIFICATION OF TUBERS FLOUR IN BANTUL DISTRICT - Rahmatika Irmasari; Subejo Subejo; Roso Witjaksono (Agro Ekonomi, 2013)
This research was done in Bantul district. The purposes of this research were to find out the response rate of village councils to the food diversification of tubers flour and the factors influencing, to find out the influence of village councils response through development of the local food process, and also to find out the influence of local food development process through the result. This research basically applied analytic descriptive method and used purposive method for sub-district and villages sampling. It took 10 village councils from each village by using simple random sampling,s o there were 60 village councils as sample in total. Data analysis has been done by proportion test, multiple regression analysis, and simple regression analysis.The result shows that mostly village councils in Bantul district have a high response on the food diversification. Government policy and motivatin on food diversification have positive influence to the response of village council. Meanwhile, age, level of education, experience, and perception do not influence to the response of village councils. The response of village councils positively influences to local food development process, and local food development process positively influences ton the result of local food development.